2011
DOI: 10.1186/1746-160x-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mechanism and principles of management of temporomandibular joint dislocation. Systematic review of literature and a proposed new classification of temporomandibular joint dislocation

Abstract: BackgroundVirtually all the articles in literature addressed only a specific type of dislocation. The aim of this review was to project a comprehensive understanding of the pathologic processes and management of all types of dislodgement of the head of the mandibular condyle from its normal position in the glenoid fossa. In addition, a new classification of temporomandibular joint dislocation was also proposed.Method and materialsA thorough computer literature search was done using the Medline, Cochrane librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
98
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 89 publications
1
98
0
10
Order By: Relevance
“…As compared with other nonsurgical and surgical techniques, ABI has the advantages of being repeatable, not requiring tissue dissection, and having fewer post-operative complications [8,15]. The uncertain nature of the pathophysiology of the procedure is the main disadvantage of ABI [9,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared with other nonsurgical and surgical techniques, ABI has the advantages of being repeatable, not requiring tissue dissection, and having fewer post-operative complications [8,15]. The uncertain nature of the pathophysiology of the procedure is the main disadvantage of ABI [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, Akinbami reported the different types of TMJ dislocations and discussed the structural factors predisposing patients to dislocation [15]. Considering the predisposing factors, patients with different dislocation frequencies might have different responses to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, age, dentition, cause and duration of the dislocation as well as the function of the masticatory muscles contribute significantly in the mechanism and management of TMJ open lock. 5) The previous studies have highlighted the predisposing and etiological factors for condyle dislocations, such as poor development of the articular fossa, laxity of the temporomandibular ligament or joint. 6) Based on such factors, various therapeutic approaches such as the introduction of a sclerosing agent into the capsular space of the TMJ, scarification of the temporalis tendon, bone grafting augmentation of articular eminence have been applied to limit the forward excursion of condyle head.…”
mentioning
confidence: 99%
“…3) TMJ dislocation or open lock, one of the TMD, has been described mainly in terms of an excessive forward movement of the condyle beyond the articular eminence with complete separation of the articular surfaces and fixation in that position. [4][5][6][7] The patient with the dislocated joint is unable to close the mouth with or without pain and this can occur as a single or chronic recurrent episode.…”
mentioning
confidence: 99%
See 1 more Smart Citation